Trajectory of Muhammadiyah Figure Nur Cholis Huda in the Indonesian Writing Arena - Affandy, Ali Nuke; Hermoyo, R. Panji; Yarno (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The last decade has seen a shift in humanities research, including literature, both in terms of theory and methods. Literature is not only analyzed based on the sociology of literary works, but also the sociology of authors with multidisciplinary theories. Everyone has a position in the social arena on which to concentrate. His position can change from ordinary to extraordinary, Or vice versa. Trajectories can be seen as the result of contestation to obtain symbolic, economic, cultural and social capital. The aim of research on the trajectory of the Indonesian Muhammadiyah figure Nur Cholis Huda (NCH) is to analyze his habitus, capital and arena. This research uses Bourdieu's qualitative descriptive praxis theory. Data collection techniques were carried out through biographical narrative interviews and data validity through triangulation. The research results show that the NCH journey is influenced by : 1). Habitual literacy is acquired from school and does not come from the family structure. 2). The ability to utilize cultural capital and convert it into economic, social and symbolic capital, and 3). Habitus literacy plus strong cultural capital supports his success in competitions in the world of writing.Thus, to understand the success of an agent/figure in an arena, it is necessary to analyze its trajectory.